Addressing Health Equity and Social Determinants of Health Through Healthy People 2030. (8th November 2021) - Gómez, Cynthia A.; Kleinman, Dushanka V.; Pronk, Nico; Wrenn Gordon, Glenda L.; Ochiai, Emmeline; Blakey, Carter; Johnson, Ayanna; Brewer, Karen H.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : The evolution of Healthy People reflects growing awareness of health inequities over the life course. Each decade, the initiative has gained understanding of how the nation can achieve health and well-being. To inform Healthy People 2030's visionary goal of achieving health equity in the coming decade, the Secretary's Advisory Committee on National Health Promotion and Disease Prevention Objectives for 2030 (Secretary's Advisory Committee) provided the US Department of Health and Human Services with guidance on key terms, frameworks, and measurement for health equity. Conditions in the environments in which people are born, live, learn, work, play, worship, and age influence health and well-being outcomes, functioning, and quality-of-life outcomes and risks and are mostly responsible for health inequities. No single individual, organization, community, or sector has sole ownership, accountability, or capacity to sustain the health and well-being of an entire population. The COVID-19 pandemic in the United States highlights underlying inequities and disparities in health and health care across segments of the population. Contributing factors that were known prior to the pandemic have led to major discrepancies in rates of infection and death. To reduce health disparities and advance health equity, systems approaches—designed to shift interconnected aspects of public health problems—are needed.